Plasma dynamics in the vicinity of the local plasma resonance point excited by pumping electric field or modulated electron beam - Anisimov, I.O.; Kelnyk, O.I.; Litoshenko, T.Eu.; Siversky, T.V.; Soroka, S.V.; Velykanets’, D.M. (Вопросы атомной науки и техники, 2006)
Excitation of the HF electric field in the local plasma resonance region (LPRR) of inhomogeneous plasma by pumping electric field or modulated electron beam results to appearance of the ponderomotive force that presses plasma out of this region. Density cavity is formed in the LPRR due to this field. Further dynamics in this region depends on the plasma properties. For plasma with hot electrons ion-acoustic pulses run away from the cavity. At the local density maximum the new peak of electric field is excited. It results to the formation of new density cavity, etc. For isothermal plasma the density jump is formed